2022
DOI: 10.14348/molcells.2022.2023
|View full text |Cite
|
Sign up to set email alerts
|

Neurons-on-a-Chip: In Vitro NeuroTools

Abstract: Neurons-on-a-Chip technology has been developed to provide diverse in vitro neuro-tools to study neuritogenesis, synaptogensis, axon guidance, and network dynamics. The two core enabling technologies are soft-lithography and microelectrode array technology. Soft lithography technology made it possible to fabricate microstamps and microfluidic channel devices with a simple replica molding method in a biological laboratory and innovatively reduced the turn-around time from assay design to chip fabrication, facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…In general, PDMS microfluidic devices that build microchannels and chambers need to be closed through the substrate to form a closed chip [124,125]. In a neural chip platform composed of an MEA and microfluidic equipment, the MEA acts as the closed substrate of the microfluidic equipment, and the microelectrode of the MEA is located in the microfluidic channel or chamber to detect electrophysiological signals [126]. This method of closing microfluidic devices and substrates is called bonding because irreversible chemical bonds are formed between the substrates and the activated or functionalized surfaces of PDMS.…”
Section: Bonding Of In Vitro Meas and Microfluidic Devicesmentioning
confidence: 99%
“…In general, PDMS microfluidic devices that build microchannels and chambers need to be closed through the substrate to form a closed chip [124,125]. In a neural chip platform composed of an MEA and microfluidic equipment, the MEA acts as the closed substrate of the microfluidic equipment, and the microelectrode of the MEA is located in the microfluidic channel or chamber to detect electrophysiological signals [126]. This method of closing microfluidic devices and substrates is called bonding because irreversible chemical bonds are formed between the substrates and the activated or functionalized surfaces of PDMS.…”
Section: Bonding Of In Vitro Meas and Microfluidic Devicesmentioning
confidence: 99%
“…Molding technology involves pouring PDMS onto a mold with microchannels, drying and solidifying, demolishing to obtain the substrate with microchannels, then packaging it by bonding, and finally making the inlet and outlet of the microfluidic chip using a PDMS punch. This method is a simple process, environmentally friendly and economical, and suitable for the generation of large quantities of chips [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies have revealed several non-random properties such as the modular architecture as a structure that is evolutionarily conserved in the nervous system ( van den Heuvel et al, 2016 ) and provided mechanistic insights into how network structure defines system functions in both normal and pathological brains ( Lynn and Bassett, 2019 ; van den Heuvel and Sporns, 2019 ; Suárez et al, 2021 ). While many studies have deciphered the structure-function relationships in the nervous system in vivo ( Meunier et al, 2010 ; Lee et al, 2016 ), recent advances in cell engineering technology using micropatterned proteins and microfluidic devices have enabled the use of cultured cells to study these relationships in a well-defined in vitro system ( Feinerman et al, 2008 ; Lewandowska et al, 2015 ; Pan et al, 2015 ; Albers and Offenhäusser, 2016 ; Yamamoto et al, 2016b , 2018 ; Forró et al, 2018 ; Hong and Nam, 2020 , 2022 ; Takemuro et al, 2020 ; Duru et al, 2022 ; Ihle et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%